Comparison of Religious Orientation and Reproductive Performance of Employed and Unemployed Women - Darooneh, Tayebeh; Saei Ghare naz, Marzieh; Hajizadeh Bandeghara, Fahimeh; kholosi, farahnaz; Nasiri, Malihe; Ozgoli, Giti (Advances in Nursing & Midwifery, 2019)
Abstract Introduction: In Iran the growing concern over low reproductive rates has led to alterations in demographic policies over recent years. The literature is indicated of different effects of women’s employed and religiosity on their reproductive performance. Present study aimed to Comprise religious orientation and reproductive performance of employed and non-employed women. Methods: This cross sectional study was conducted on 360 unemployed and employed women in healthcare centers affiliated to Shahid Beheshti University of Medical Sciences and in schools of selected districts of Ministry of Education in Tehran, 2015. Three questionnaires including: demographic characteristics, religious orientation and reproductive performance were utilized for data collection. Results: The Mean ± SD number of children for unemployed women was 1.29±0.75, for women working at schools 1.68±0.71 and those working in healthcare centers was 1.08± 0.84 (P=0.001). The mean ideal number of children for women working at schools was significantly higher than that of unemployed women and employed women in healthcare centers and hospitals (P=0.001). The level of gender preference for a male child in the housewife group 21.7% (39) was higher than that of the employed groups and the majority of employed women in Ministry of Health 61.1%(55) and Ministry of Education 70%(63) had no gender preferences. Intention for childbearing in unemployed women 43.3% (78) was higher than in the employed ones. Religious orientation had significant and positive correlation with the number of children (P = 0.01, r = 0.13). Conclusions: Women’s employed is associated with their religious orientation and reproductive performance. This research took steps to identify the factors affecting the success of demographic policies.